Knowledge, attitudes and practices on risk factors of non-communicable diseases (NCDs): a cross-sectional survey among urban and rural adults in Negeri Sembilan, Malaysia - Ithnin, Muslimah; Juliana, Norsham; Mohd Effendy, Nadia; Sahar, Mohd Azmani; Abang Abdullah, Khadijah Hasanah; Muhammad Shamsir Mohd Aris; Mohd Rani, Mohd Dzulkhairi; Nadeeya'ayn Umaisara Mohamad Nor (Universiti Sains Islam Malaysia, 2024)
Indexed by Scopus